2005
DOI: 10.1111/j.1469-8137.2005.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel herbicide oxaziclomefone inhibits cell expansion in maize cell cultures without affecting turgor pressure or wall acidification

Abstract: Summary• Oxaziclomefone [OAC; IUPAC name 3-(1-(3,5-dichlorophenyl)-1-methylethyl)-3,4-dihydro-6-methyl-5-phenyl-2 H -1,3-oxazin-4-one] is a new herbicide that inhibits cell expansion in grass roots. Its effects on cell cultures and mode of action were unknown. In principle, cell expansion could be inhibited by a decrease in either turgor pressure or wall extensibility.• Cell expansion was estimated as settled cell volume; cell division was estimated by cell counting. Membrane permeability to water was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These processes include: cellulose biosynthesis; wall matrix polysaccharide biosynthesis, including MLG; production, secretion and action of XET activity; production, secretion and action of peroxidase activity; polysaccharide feruloylation; oxidative coupling of feruloyl or p-coumaroyl residues; and consumption of apoplastic ascorbate, a potential source of ƒ OH radicals. In addition, it had been shown previously (O'Looney and Fry, 2005) that OAC does not interfere with the cells' ability to acidify their medium (which may be necessary for 'acid growth').…”
Section: Effect Of An Oac Analogue On Mlg and Starch Biosynthesismentioning
confidence: 98%
See 1 more Smart Citation
“…These processes include: cellulose biosynthesis; wall matrix polysaccharide biosynthesis, including MLG; production, secretion and action of XET activity; production, secretion and action of peroxidase activity; polysaccharide feruloylation; oxidative coupling of feruloyl or p-coumaroyl residues; and consumption of apoplastic ascorbate, a potential source of ƒ OH radicals. In addition, it had been shown previously (O'Looney and Fry, 2005) that OAC does not interfere with the cells' ability to acidify their medium (which may be necessary for 'acid growth').…”
Section: Effect Of An Oac Analogue On Mlg and Starch Biosynthesismentioning
confidence: 98%
“…Cell expansion is driven by turgor pressure, and in healthy tissues is usually limited by the extensibility of the cell wall or sometimes by the wall yield threshold (Cosgrove, 1993;Kutschera, 2001). In recent work (O'Looney and Fry, 2005) it was found that OAC inhibits cell expansion in maize cell cultures, with an ID 50 (dose causing 50 % inhibition) of approx. 5 nM.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these symptoms and to other physiological responses, it was stated that Integrative theory of the mode of action of quinclorac: literature review these responses would be associated to the inhibition of the cellular expansion (Koo et al, 1996). Similar effects are found in other herbicides that inhibit cell wall synthesis, such as oxaziclomefone (O'Looney & Fry, 2005) and diclobenil (Peng et al, 2001;DeBolt et al, 2007;Wightman & Turner, 2010).…”
Section: Effect On the Formation Of The Cellular Wallmentioning
confidence: 89%
“…So far, the MoA of oxaziclomefone has remained elusive 35,36 and it is therefore classified in the HRAC class 0. Here, we present data on oxaziclomefone that show strong FAT thermal stabilization, strong FAT binding in the active center, strong inhibition of FFA production in the FAT activity assay and the clear FAT-like fingerprint in the P-Profile.…”
Section: Discussionmentioning
confidence: 99%